The role of physical activity in preventing cognitive decline among U.S. older adults with diabetes and prediabetes: a cross-sectional study - Wang, Yifei; Liu, Dezheng; Wang, Hongli; Wang, Mengzhao; Ruan, Weiqi; Han, Yanbai; Han, Yiming (Frontiers in Public Health, 2025)
BackgroundPhysical activity (PA) has been widely recognized as a key strategy to slow age-related cognitive decline. However, its specific effects on older adults with diabetes or prediabetes remain poorly understood. Therefore, we investigated the association between different levels of PA and cognitive function among older Americans with diabetes and prediabetes.MethodsThis cross-sectional study used data from the 2011–2014 National Health and Nutrition Examination Survey (NHANES) and included a total of 1,299 older adults aged ≥60 years. The PA levels were determined by calculating the weekly metabolic equivalent of task time (MET-min/week). The participants’ cognitive abilities were assessed using the Consortium to Establish a Registry for Alzheimer’s disease (CERAD) Word Learning Test, Animal Fluency Test (AFT), and Digit Symbol Substitution Test (DSST). Multivariable logistic regression models were used to analyze the association between different PA levels and cognitive function in patients with diabetes and prediabetes. The study utilized the restricted cubic spline (RCS) models to explore the nonlinear correlation of PA with cognitive function.ResultsUpon controlling for confounders, DSST scores were still significantly associated with moderate-level PA (OR: 0.457, 95% CI: 0.244, 0.853, p = 0.020) and high-level PA (OR: 0.478, 95% CI: 0.240, 0.955, p = 0.039). According to the RCS models, PA showed a significant nonlinear correlation with cognitive function, and the risk of cognitive decline decreased with the increase of PA levels.ConclusionIn older adults with diabetes and prediabetes, moderate and high levels of physical activity are associated with a lower risk of cognitive decline. Clinicians should encourage patients to participate actively in exercise to maximize the benefits of PA.